SCIPA Switch-On: A Randomized Controlled Trial Investigating the Efficacy and Safety of Functional Electrical Stimulation–Assisted Cycling and Passive Cycling Initiated Early After Traumatic Spinal Cord Injury. (June 2017) - Galea, Mary P.; Panisset, Maya G.; El-Ansary, Doa; Dunlop, Sarah A.; Marshall, Ruth; Clark, Jillian M.; Churilov, Leonid
Background. Substantial skeletal muscle atrophy after spinal cord injury (SCI) carries significant repercussions for functional recovery and longer-term health. Objective. To compare the efficacy, safety, and feasibility of functional electrical stimulation–assisted cycling (FESC) and passive cycling (PC) to attenuate muscle atrophy after acute SCI. Methods. This multicenter, assessor-blinded phase I/II trial randomized participants at 4 weeks post-SCI to FESC or PC (4 sessions per week, 1 hour maximum per session, over 12 weeks). The primary outcome measure was mean maximum cross-sectional area (CSA) of thigh and calf muscles (magnetic resonance imaging), and secondary outcome measures comprised body composition (dual energy X-ray absorptiometry), anthropometry, quality of life, and adverse events (AEs). Results. Of 24 participants, 19 completed the 12-week trial (10 FESC, 9 PC, 18 male). Those participants completed >80% of training sessions (FESC, 83.5%; PC, 85.9%). No significant between-group difference in postintervention muscle CSA was found. No significant between-group difference was found for any other tissue, anthropometric parameter, or behavioral variable or AEs. Six participants experienced thigh hypertrophy (FESC = 3; PC = 3). Atrophy was attenuated (<30%) in 15 cases (FESC = 7; PC = 8). Conclusions. Both cycle ergometry regimens examined were safe, feasible, and well tolerated early after SCI. No conclusions regarding efficacy can be drawn from our data. Further investigation of both modalities early after SCI is required.